Stature and status: Height, ability, and labor market outcomes - Case, Anne (2008)
The well-known association between height and earnings is often thought to reflect factors such as self esteem, social dominance, and discrimination. We offer a simpler explanation: height is positively associated with cognitive ability, which is rewarded in the labor market. Using data from the US and the UK, we show that taller children have higher average cognitive test scores, and that these test scores explain a large portion of the height premium in earnings. Children who have higher test scores also experience earlier adolescent growth spurts, so that height in adolescence serves as a marker of cognitive ability.